|x|=|x-y+y|<=|x-y|+|y| -> |x|-|y|<=|x-y|
Likewise |y-x|<=|y|-|x| -> |x|-|y|>= -|y-x|= -|x-y|
Suppose that x<>y. Then |x-y|>0 so let e=|x-y|.
I follow problem one of what you did really well. I am confused on 3
what is x<>y....does this just mean x = y, also why are you letting e = |x-y|, doesnt it say e is less than that....I know I am completely wrong because you have been right ever since you have started helping me. Maybe if you could explain it I would understand
Should these questions be easier for me to answer? I mean you guys come up with the solutions really quickly and I spend hours without even figure out how to do it. But I am at the average as far as grades for the course so I guess im not the only one struggling in the class.